Internet banking acceptance in the United States and Malaysia: a cross-cultural examination - Yuen, Y.Y.; Yeow, P.; Lim, Nena (Emerald Group Publishing Limited, 2015)
Purpose: The purpose of this paper is to investigate the cultural differences in internet banking adoption between the USA and Malaysia. It aims to provide marketing recommendations based on specific cultural dimensions to promote internet banking. Design/methodology/approach: With four added variables (attitude towards use, perceived credibility, self-efficacy, and anxiety), the Unified Theory of Acceptance and Use of Technology model was used. A questionnaire was developed based on the research model and distributed to 1,050 internet banking users from two countries. Structural equation modelling (SEM) was applied to 666 valid questionnaires to test the research hypotheses.Findings: Results show that due to cultural differences, global consumers have different internet banking adoption patterns. Consumers in the USA have a more positive attitude towards use. Moreover, perceived credibility plays an important role in influencing internet banking in the USA. On the other hand, performance expectancy has a direct influence on internet banking adoption in Malaysia. Cultural dimensions such as individualism/collectivism, power distance, uncertainty avoidance, monochromic/polychromic, and high context/low context were used to explain these findings. Based on the findings, marketing recommendations that help promote internet banking in both countries were provided. Originality/value: This is the one of the pioneer studies that highlights the importance of cultural differences in promoting internet banking services. It contributes to the literature by developing and testing a comprehensive research model using SEM.